The relationship between vocabulary and viewing comprehension. (February 2020) - Durbahn, Marion; Rodgers, Michael; Peters, Elke
Abstract: The present study explores the relationship between lexical coverage and viewing comprehension. The study also addresses the role of imagery in viewing comprehension by distinguishing between audio-based, audio plus imagery-based, and imagery-based comprehension questions. Learners' lexical coverage was determined by measuring participants' knowledge of the words occurring in the documentary in an aural-meaning recall test, whereas viewing comprehension was measured by means of literal and inferential comprehension questions. One hundred and fourteen EFL learners took part in the study. Results showed an almost medium-sized correlation between lexical coverage and viewing comprehension ( r s (94) = .39). Results also showed a positive almost medium-sized correlation between audio-based questions and lexical coverage ( r s (94) = .36), and a small-sized correlation between imagery-based questions and lexical coverage ( r s (94) = .29). No relationship was observed between lexical coverage and imagery plus audio-based questions. No threshold for minimum comprehension was observed. The results indicate that the lexical demands for viewing are lower than those for reading but similar to those for listening. Implications for pedagogy and future research are discussed. Highlights: Lexical coverage of documentaries is moderately related to viewing comprehension. The demands for viewing documentaries are lower than for reading texts. Lexical coverage plays a more fundamental role in audio-based question.